Organizational Network Evolution and Governance Strategies in Megaprojects (Construction Economics and Building, 2015)
The organization is the key factor for megaprojects in which thousands of connections and relations intertwine and influence the project performance. However, organizational evolution in megaprojects has not been fully studied. This study investigates the evolution of the organizational network of a megaproject in China using social network analysis (SNA), and then proposes corresponding governance strategies. The result shows that megaproject organizations evolve towards more connected networks but are differentiated for various investors. For government invested projects, the organizational network is well connected, cooperative, yet unstable and require strategic long-term governance policies; for private invested projects, the network is stable, but collaboration among participants is low, which indicates a need to establish collaborative governance structures. The result complements the organizational evolution theory for megaprojects and offers effective strategies for governing megaproject organizations. This study also helps practitioners better understand the nature and characteristics of megaproject organizations.